Method of Application of Support Vector Regression In Predicting The Number of Visits of Foreign Tourists to The Province of Maluku - Wahyuni Aprilya; Marlon S. N. Van Delsen; M. Y. Matdoana (Indonesian Journal of Artificial Intelligence and Data Mining, 2023)
Maluku Province is one of the areas in Indonesia that has many tourist attractions to visit, both natural and cultural heritage. The high interest of foreign tourists who want to visit various tourist objects, makes the tourism industry able to bring benefits and profits for most of the people of Maluku. However, in the last two years, 2020-2021, all countries were faced with the Covid-19 pandemic. The Covid-19 pandemic has resulted in a decrease in the number of foreign tourist visits to Indonesia. To increase marketing activities in the midst of the Covid-19 pandemic that has hit Indonesia since 2020, foreign tourist information is increasingly needed as material for evaluation and planning for future development. One of the methods used to predict the number of foreign tourist visits to Maluku Province is Support Vector Regression (SVR). Based on forecasting using test data, the RMSE value is 1.334985 and the MAPE obtained is 1.256346%, so the prediction of the number of foreign tourist visits to Maluku Province in 2022 (January-June) states that in January the number of tourist visits was 999 hundred visits. and increased until June as many as 1121 thousand visits.